2011
DOI: 10.5114/pwki.2011.21187
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous mitral commissurotomy in pregnant women – long-term observations

Abstract: A b s t r a c tBackground: Percutaneous mitral commissurotomy (PMC) can be safely performed during pregnancy. However, there is still little known about follow-up results after PMC in populations of pregnant women taking into consideration childhood development.Aim: To evaluate long-term clinical follow-up and echocardiographic data on pregnant patients who underwent PMC in our centre and development of their infants.Material and methods: From January 1989 to December 1998, 15 pregnant women with mitral stenos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Three additional studies were identified through reference search of the included studies. Altogether, 21 articles were finally included in the review, after excluding one article from the same author with an overlap in the time period of inclusion of cases 18‐38 . Characteristics of the studies are shown in Table .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three additional studies were identified through reference search of the included studies. Altogether, 21 articles were finally included in the review, after excluding one article from the same author with an overlap in the time period of inclusion of cases 18‐38 . Characteristics of the studies are shown in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Thrombus formation during the procedure itself or air embolism increases the risk of thromboembolic events. Left to right shunts following septal puncture usually resolve over time or reduce in size 18,24,26,27,29,36 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[191] ES was also found having positive effects on alopecia cue to electrotrichogenesis, which could enhance the influx of calcium ions into the dermal papilla cells via voltage-gated transmembrane ion channels, facilitate ATP synthesis in mitochondria, activate protein kinases, and stimulate protein synthesis and cell division. [192][193][194] Based on the proven therapeutic effects of traditional ES on hair growth, Yao et al fabricated a universal motion-activated ES device (m-ESD) that could effectively promote hair regeneration via random body motions. [195] Similar to the wound healing bandage, the m-ESD also consisted of two modules, including an omnidirectional TENG acting as the electric pulse generator and a pair of interdigitated dressing electrode providing spatially distributed electric fields (Figure 7b).…”
Section: Electroceuticals For Skin Regenerationmentioning
confidence: 99%
“…Percutaneous mitral balloon valvuloplasty (MBV) is an effective therapeutic choice for suitable cases [5]. The MBV is ever effective in unsuitable situations for surgery [6]. The LA dysfunctions in mitral stenosis (MS) and subsequent recovery following successful MBV have been documented by conventional echocardiographic methods [4,7].…”
Section: Introductionmentioning
confidence: 99%